Facially Polarized Molecule for Alkalides and Superalkalides with Considerable Nonlinear Optical Response. Issue 45 (4th December 2018) - Li, Bo; Peng, Daoling; Gu, Feng Long; Zhu, Chaoyuan
Abstract: In this work, alkali M (Li and K) and superalkali M′3 O (M′=Li and Na) combined with facially polarized molecule, all‐cis 1, 2, 3, 4, 5, 6‐Hexafluorocyclohexane (L, C6 H6 F6 ), were utilized to design novel alkalides L‐M‐L‐M′ and superalkalides L‐M‐L‐M′3 O, respectively. Computational results show that alkalides L‐M‐L‐M′ and superalkalides L‐M‐L‐M′3 O have high thermodynamic stability, and the superalkalides L‐M‐L‐M′3 O are more stable than the alkalides L‐M‐L‐M′. Importantly, they also possess remarkable NLO responses, the electronic contribution of the static first hyperpolarizability ( β 0 e ) has upped to 3.42×10 6 (a.u.) for L‐K‐L‐Li3 O. In particularly, the number of ligand L considerably impacts on β 0 e value, namely, the β 0 e value of Li‐L‐Li3 O can be improved two orders of magnitude by adding additional ligand L, 1.31×10 6 (a.u.)(L‐Li‐L‐Li3 O) > 7.76×10 4 (a.u.)(Li‐L‐Li3 O). We hope this work can attract researchers to design and synthesize novel excess electron compounds with high performance NLO materials. Abstract : Facially polarized molecule, all‐cis 1, 2, 3, 4, 5, 6‐Hexafluorocyclohexane, is utilized to design alkalides and superalkalides with considerable nonlinear optical responses.